Force induced melting of the constrained DNA - Singh, A.R.; Giri, D.; Kumar, S. (My University, 2010)
We develop a simple model to study the effects of the applied force on the melting of a double stranded DNA (dsDNA). Using this model, we could study the stretching, unzipping, rupture and slippagelike transition in a dsDNA. We show that in absence of an applied force, the melting temperature and the melting profile of dsDNA strongly depend on the constrained imposed on the ends of dsDNA. The nature of the phase boundary of the force-temperature diagram, which separates the zipped and the open state for the shearinglike transition is remarkably different than the DNA unzipping.
Keywords: Double-stranded DNA (ds-DNA); Force-induced melting; biomechanics; transition temperature